2018
DOI: 10.1590/1806-90882017000600006
|View full text |Cite
|
Sign up to set email alerts
|

WATER EROSION UNDER THREE TILLAGE METHODS IN A CULTIVATION OF Eucalyptus benthamii

Abstract: -Soil tillage influences the development of forests planted in the initial phase, which affects some hydrological processes and water erosion. The objective of this study was to quantify the water losses (WL) and soil losses (SL) by water erosion, between the second and third years of eucalyptus (Eucalyptus benthamii) crop, in an experiment located in southern Brazil, on a Humic Dystrudept. Was study three soil tillage treatments: i) subsoiling in downslope direction (SD); ii) subsoiling in contour on the slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This justifi es the adoption of supportive conservation practices to hold these losses, storing runoff water within the cultivation area. In percentage terms, the total annual WLs showed very low values compared to the height of the rains, varying between 0.020% and 0.058%, therefore, substantially lower than the WLs verifi ed by Magro et al (2011) and Padilha et al (2017). Magro et al (2011) and Padilha et al (2017) found SL values of up to 19,700 kg ha -1 and 520 kg ha -1 , respectively.…”
Section: Treatment Phosphorus Potassium Phosphorusmentioning
confidence: 74%
See 3 more Smart Citations
“…This justifi es the adoption of supportive conservation practices to hold these losses, storing runoff water within the cultivation area. In percentage terms, the total annual WLs showed very low values compared to the height of the rains, varying between 0.020% and 0.058%, therefore, substantially lower than the WLs verifi ed by Magro et al (2011) and Padilha et al (2017). Magro et al (2011) and Padilha et al (2017) found SL values of up to 19,700 kg ha -1 and 520 kg ha -1 , respectively.…”
Section: Treatment Phosphorus Potassium Phosphorusmentioning
confidence: 74%
“…In percentage terms, the total annual WLs showed very low values compared to the height of the rains, varying between 0.020% and 0.058%, therefore, substantially lower than the WLs verifi ed by Magro et al (2011) and Padilha et al (2017). Magro et al (2011) and Padilha et al (2017) found SL values of up to 19,700 kg ha -1 and 520 kg ha -1 , respectively. The low SL values verifi ed in this research are due to the same factors that contributed to the low WL, that is, the canopy of the plants, the vegetal mass in the form of litter and the galleries in the soil opened by the roots.…”
Section: Treatment Phosphorus Potassium Phosphorusmentioning
confidence: 74%
See 2 more Smart Citations
“…Several studies have tried to identify and measure gains or losses in water services to get realistic sceneries with high-quality data (KEELER et al, 2012;OJEA, MARTIN-ORTEGA, 2015, LA NOTTE et al, 2015ZHENG et.al, 2016;DING et al, 2016), many present monetary valuation techniques aiming at better policy choices (DI SABATINO et al, 2013;OJEA, MARTIN-ORTEGA, 2015, LA NOTTE et al, 2015.…”
Section: Introductionmentioning
confidence: 99%